Selective Modulation of TNF–TNFRs Signaling: Insights for Multiple Sclerosis Treatment - Pegoretti, Valentina; Baron, Wia; Laman, Jon D.; Eisel, Ulrich L. M. (Frontiers in Immunology, 2018)
Autoimmunity develops when self-tolerance mechanisms are failing to protect healthy tissue. A sustained reaction to self is generated, which includes the generation of effector cells and molecules that destroy tissues. A way to restore this intrinsic tolerance is through immune modulation that aims at refurbishing this immunologically naïve or unresponsive state, thereby decreasing the aberrant immune reaction taking place. One major cytokine has been shown to play a pivotal role in several autoimmune diseases such as rheumatoid arthritis (RA) and multiple sclerosis (MS): Tumor Necrosis Factor alpha (TNFα) modulates the induction and maintenance of an inflammatory process and it comes in two variants, soluble TNF (solTNF) and transmembrane bound TNF (tmTNF). TmTNF signals via TNFR1 and TNFR2, whereas solTNF signals mainly via TNFR1. TNFR1 is widely expressed and promotes mainly inflammation and apoptosis. Conversely, TNFR2 is restricted mainly to immune and endothelial cells and it is known to activate the pro-survival PI3K-Akt/PKB signaling pathway, and to sustain regulatory T cells function. Anti-TNFα therapies are successfully used to treat diseases such as RA, colitis and psoriasis. However, clinical studies with a non-selective inhibitor of TNFα in MS patients had to be halted due to exacerbation of clinical symptoms. One possible explanation for this failure is the non-selectivity of the treatment, which avoids TNFR2 stimulation and its immune and tissue protective properties. Thus, a receptor-selective modulation of TNFα signal pathways provides a novel therapeutic concept that might lead to new insights in MS pathology with major implications for its effective treatment.